Antioxidant potential of cucurbita maxima extract as affected by pretreatment, solvent extraction and drying process / Iswaibah Mustafa - Mustafa, Iswaibah; Mohd Sukhri, Nurul Afieqah; Zuhaire, Farra Batrisyia Zaiba; Muhammad Shamsudin Kiong, Norazila; Mohamad Zin, Mohamad Imran
Pumpkin (Cucurbita maxima) is one of the classified fruits that contains a lot of beneficial properties that could contribute to health. However, most usage of pumpkin from its fresh form is prone to microorganisms' spoilage. The main purpose of this study was systematically to evaluate the Total Phenolic Contents (TPC) of pumpkin extracts as affected by pre-treatment, solvent extraction and drying process. Therefore, four different objectives were applied. The first objective is conducted by oven-drying with different temperatures (0°C, 40°C and 80°C). The dried extracts of 40°C and 80°C are compared to untreated or fresh pumpkin (0°C). The second objective is carried out by using different methods of drying (oven-drying, sun-drying and shade-drying). The TPC of these dried pumpkins were evaluated. The third objective is conducted by using different green solvents (ethanol, aqueous ethanol and methanol). The concentration of extracted bioactive compounds is greatly influenced by the solvent used to extract bioactive compounds from the pumpkin since the compounds have different properties and polarities. The last objective is carried out by using different blanching methods (blanching, non- blanching). Blanching method was applied to preserve the bioactive compounds in the pumpkin and the results were monitored. Results obtained for every objective respectively; in the first objective, oven-drying at 40C increased the value of TPC. However, at 80°C the TPC were enhanced significantly compared to the fresh ones. In the second objective, all three drying methods caused loss of TPC. However, the least reduction of TPC can be seen by oven-drying at certain temperature. Next, in the third objective, aqueous ethanol has the highest TPC compared to ethanol and methanol. The last objective shows that blanching method helps in preserving the bioactive compounds. This can be proved by the result in which blanching have the highest TPC compared to non-blanching. Through the ANOVA statistical analysis, objective 1 has the highest F-value with 70883.93 which shows that temperature gave significant effects of TPC compared to solvent extraction with F-value of 3700.5 and followed by different drying methods with F-value of 56.43. Pre-treatment has the least effects on TPC with the lowest F-value which is 5.09.